RESEARCH OF FORMATION OF THE MOTIVATIONAL VALUE COMPONENT OF INFORMATION CULTURE OF FUTURE BACHELOR OF PHILOLOGY - Hlushak, Oksana M. (Educological discourse, 2014)
The article describes the components of the information culture of the future bachelors Philology: motivational-value, cognitive, professional-technological, evaluative-effective. Characterized motivational-value component of information culture of bachelors of philology. The study found that the students of the experimental and control groups, the levels of formation of information culture motivational criteria differ significantly: for students of the experimental group is characterized by active and effective attitude towards the use of ICT in teaching and learning and professional activities for students of control group is characterized by the active- positive attitude towards the organization of teaching and learning of ICT.